THE CHARACTERISTICS OF: A SINGAPOREAN SCIENCE TEXTBOOK WRITTEN IN ENGLISH FOR PRIMARY-THREE AND FOUR - Linggayani Soentoro (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
Textbooks play an important role in teaching learning process. Teachers and students can be well-equipped with the textbooks as the sources of knowledge, guidance and activities. As Indonesia has been aware of the use of imported books to upgrade their curriculum to be international standardized, the primary students are one of the subjects to use these books, especially those who study at International, International Standardized and Immersion program in National Schools. The generic structure and the physical characteristics of the textbooks build special attractiveness and images to the readers, in this case young learners in Indonesia in the science class. This paper discusses the presentation of the Singaporean science textbooks written in English and the appropriateness of the books for for Indonesian students.